Development of an intravital imaging system for the synovial tissue reveals the dynamics of CTLA-4 Ig in vivo - Tetsuo Hasegawa (Nature Portfolio, 2020)
Abstract There have been many attempts to visualize the inflamed joints using multiphoton microscopy. However, due to the hypervascular and multilayered structure of the inflamed synovium, intravital imaging of the deep synovial tissue has been difficult. Here, we established original intravital imaging systems to visualize synovial tissue and pathological osteoclasts at the pannus–bone interface using multiphoton microscopy. Combined with fluorescence-labeling of CTLA-4 Ig, a biological agent used for the treatment of rheumatoid arthritis, we identified that CTLA-4 Ig was distributed predominantly within the inflamed synovium and bound to CX3CR1+ macrophages and CD140a+ fibroblasts 6 h after injection, but not to mature osteoclasts. Intravital imaging of blood and lymphatic vessels in the inflamed synovium further showed that extravasated CTLA-4 Ig was immediately drained through lymphatic vessels under acute arthritic conditions, but the drainage activity was retarded under chronic conditions. These results indicate that this intravital synovial imaging system can serve as a platform for exploring the dynamics of immune cells, osteoclasts, and biological agents within the synovial microenvironment in vivo.